The off-farm income and organic food expenditure nexus: Empirical evidence from rural Ghana - Martinson Ankrah Twumasi; Hongyun Zheng; Isaac Owusu Asante; Evans Brako Ntiamoah; Gideon Amo-Ntim (Cogent Food & Agriculture, 2023)
AbstractThis study uses evidence gathered from survey responses from 572 rural households in Ghana to examine the link between organic expenditure and off-farm income. To solve the endogeneity problem related to off-farm income, we use the instrumental variable Tobit model. The findings showed that expenditure on organic food was strongly and favorably connected to off-farm income. According to the disaggregated findings, female off-farm income is significantly more positively correlated with organic food expenditure than male off-farm income. The results provide practical implications for facilitating organic food consumption and eliminating food and nutrition insecurity among rural dwellers.